Advances in the Study of Bacterial-mediated Antitumor Therapy - Liu, Jing (International Journal of Public Health and Medical Research, 2025)
Tumors, due to their complex pathophysiological properties and potential drug resistance, make it difficult for traditional treatment modalities, including radiotherapy, chemotherapy and immunotherapy, to completely eliminate tumor cells. As an emerging therapeutic strategy, bacteriotherapy demonstrates its unique advantages, which are highly targeted. Whether applied alone or in combination with nanotechnology, bacterial therapy can effectively prevent tumor recurrence and metastasis. With the help of genetic engineering technology, it is possible to enable bacteria to express anti-cancer drugs, and these bacteria are able to precisely target the tumor area and release therapeutic molecules to induce apoptosis of tumor cells. Bacteria-targeted therapy has great potential for development in the field of tumor therapy. The paper reviews the research progress of bacterial therapies, introduces the principle of various bacterial therapies for tumor treatment, the research progress of bacterial therapies combined with nanotechnology, and the limitations of this therapy.